Fornisländsk litteratur, genetik och historisk demografi om samisk-nordiska tidiga kontakter - Kusmenko, Jurij (Scandinavistica Vilnensis, 2019)
Old Icelandic literature, genetics and historical demography regarding Sámi-Scandinavian early contacts The spreading of Sámi interference features to the North Germanic languages is confirmed not only by the Old Icelandic sagas, which show us an absolute acceptance of the Sámi in the North Germanic society and marriages between the two nations, but also by the populational genetics that show that the percentage of the “Sámish” haplogroups (Y-DNA N1c, mtDNA U5 and V) among the North Germanic people exceeds considerably the percentage of the modern Sámi population, which indicates a language shift and assimilation of a part of the Sámi (especially of the Southern Sámi). Changes in the population structure caused by two pest pandemics (in the seventh to ninth and in the fourteenth and fifteenth centuries) that affected Northern and Central Scandinavia to a much lesser degree could also contribute both to the spreading of the Sámi genes in Northern and Central Scandinavia and of the Sámi interference features in the North Germanic languages.